2002
DOI: 10.1097/00000542-200211000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Sulfite Supported Lipid Peroxidation in Propofol Emulsions

Abstract: These results show that sulfite supports the peroxidation of lipids in soybean oil emulsions and propofol functions to partially inhibit these processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…Sulfite derivatives have been shown to generate oxidative stress in several investigations (Baker et al, 2002;Ercan et al, 2010;Meng, 2003 ). The underlyin g mechanism of sulfite-induced oxidative stress is thought to initiate with the oxidation of sulfite (SO À2…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfite derivatives have been shown to generate oxidative stress in several investigations (Baker et al, 2002;Ercan et al, 2010;Meng, 2003 ). The underlyin g mechanism of sulfite-induced oxidative stress is thought to initiate with the oxidation of sulfite (SO À2…”
Section: Discussionmentioning
confidence: 99%
“…The sulfite radical can subsequent ly react with molecular oxygen to form sulfite peroxyl radical and sulfate radical, which in turn reacts with lipids (Zaloga and Marik, 2003 ). Addition ally, sulfite radicals can also directly react with lipids resulting in the formation of a lipid alkyl radical (Baker et al, 2002 ). In physiological conditions, cells cope with free radicals using enzymatic and nonenzyma tic defenses such as superoxi de dismutase (SOD), glutathione peroxidase (GP x ), catalase (CAT), and glutathione (GSH) (Meng, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…and SO-deficient rats (Chiarani et al, 2008;Derin et al, 2009;Herken 77 et al, 2009;Küçükatay et al, 2005;Ozturk et al, 2010). Moreover,78 chemical studies demonstrated that sulfite generates a sulfite radical 79 that could mediate lipid peroxidation, and leads to the formation of 80 superoxide anion in the presence of oxygen (Baker et al, 2002; 81 Mottley and Mason, 1988). It has been shown also that sulfite decreases 82 mitochondrial membrane potential and ATP synthesis in mitochondria 83 prepared from rat brain and kidney, as well as in Neuro-2a and PC12 84 cells (Vincent et al, 2004;Zhang et al, 2004) …”
Section: Reactive Speciesmentioning
confidence: 99%
“…Likewise, several researches in the literature reported the fact that sulfite treatment increases lipid peroxidation (Baker et al, 2002;Derin et al, 2009;Derin et al, 2006;Kaplan et al, 1975;Ozturk et al, 2011). Mechanisms of sulfite-induced lipid peroxidation are thought to initially involve SO 3 À2 oxidation into a sulfite radical (SO 3 + ) (Baker et al, 2002;Fridovich and Handler, 1959).…”
Section: Discussionmentioning
confidence: 99%